Intramembranous processing by γ‐secretase regulates reverse signaling of ephrin‐B2 in migration of microglia. Issue 7 (3rd April 2017) - Kemmerling, Nadja; Wunderlich, Patrick; Theil, Sandra; Linnartz‐Gerlach, Bettina; Hersch, Nils; Hoffmann, Bernd; Heneka, Michael T.; de Strooper, Bart; Neumann, Harald; Walter, Jochen
Abstract: The Eph‐ephrin system plays pivotal roles in cell adhesion and migration. The receptor‐like functions of the ephrin ligands allow the regulation of intracellular processes via reverse signaling. γ‐Secretase mediated processing of ephrin‐B has previously been linked to activation of Src, a kinase crucial for focal adhesion and podosome phosphorylation. Here, we analyzed the role of γ‐secretase in the stimulation of reverse ephrin‐B2 signaling in the migration of mouse embryonic stem cell derived microglia. The proteolytic generation of the ephrin‐B2 intracellular domain (ICD) by γ‐secretase stimulates Src and focal adhesion kinase (FAK). Inhibition of γ‐secretase decreased the phosphorylation of Src and FAK, and reduced cell motility. These effects were associated with enlargement of the podosomal surface. Interestingly, expression of ephrin‐B2 ICD could rescue these effects, indicating that this proteolytic fragment mediates the activation of Src and FAK, and thereby regulates podosomal dynamics in microglial cells. Together, these results identify γ‐secretase as well as ephrin‐B2 as regulators of microglial migration. Main Points: γ‐Secretase cleaves ephrin‐B2 in microglia. The ephrin‐B2 intracellular domain regulates phosphorylation of Src/FAK, podosomal dynamics, and microglial motility. γ‐Secretase regulates reverse signalling of ephrin‐B2 in microglia.